Analisis Pendapatan Asli Daerah Di Daerah Istimewa Yogyakarta - Nailia Kamalia; Rifki Khoirudin (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2019)
This research was conducted in order to determine what factors are affecting the regional revenue in the province in particular districts/cities in 2010-2017. In this study, the variables used are local revenue as the dependent variable. Then the independent variable is the number of tourists, the number of people, capital expenditures, and the number of hotels. This study uses panel data, which is a combination of time series in the form of a sequence of years 2010-2017 and cross-section in the form of latitude Regency / City in the province, with a total of 40 observations observation. The results of this study stated that the most appropriate model used is the fixed effect